2019
DOI: 10.1371/journal.pone.0226512
|View full text |Cite
|
Sign up to set email alerts
|

Previously implanted mitral surgical prosthesis in patients undergoing transcatheter aortic valve implantation: Procedural outcome and morphologic assessment using multidetector computed tomography

Abstract: Transcatheter aortic valve implantation (TAVI) in the presence of a preexisting mitral prosthesis is challenging and its influence on the morphology of mitral prosthesis and the positioning of transcatheter heart valve (THV) is unknown. We assessed the feasibility of TAVI for patients with preexisting mitral prostheses, its influence on mitral prosthesis morphology, and the positional interaction between a newly implanted THV and mitral prosthesis using serial multidetector computed tomography (MDCT). Thirty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, it remains an intervention with potential catastrophic complications, including device embolization or malposition, mainly due to the migration of the aortic prosthesis during implantation 10 . THV migration is associated with large native aortic annulus, 11 low calcific burden and predominant aortic regurgitation. The risk of aortic THV under‐expansion and the MMP dysfunction is related to the interaction between the prosthesis stent frame and the distal edge of the THV.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it remains an intervention with potential catastrophic complications, including device embolization or malposition, mainly due to the migration of the aortic prosthesis during implantation 10 . THV migration is associated with large native aortic annulus, 11 low calcific burden and predominant aortic regurgitation. The risk of aortic THV under‐expansion and the MMP dysfunction is related to the interaction between the prosthesis stent frame and the distal edge of the THV.…”
Section: Discussionmentioning
confidence: 99%
“…Mean THV pressure gradient immediately and 6 months after TAVR was slightly higher in patients with prior MVR (12.86 mmHg and 13.54 mmHg) than without prior MVR (11.23 mmHg and 10.53 mmHg) though statistically not significant (p = 0.144 and p = 0.062). 12) Tanaka et al reported that the incidence of THV stenosis was 6.5% and grade 3 or 4 PVL was 3.2% among 31 patients with prior MVR, respectively. 12) In recent prospective trials, grade 3 or 4 PVL has been improved to 2% to 3% simply due to newer TAVR devices.…”
Section: Thv Dysfunctionmentioning
confidence: 99%
“…12) Tanaka et al reported that the incidence of THV stenosis was 6.5% and grade 3 or 4 PVL was 3.2% among 31 patients with prior MVR, respectively. 12) In recent prospective trials, grade 3 or 4 PVL has been improved to 2% to 3% simply due to newer TAVR devices. 7)…”
Section: Thv Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations